Mycoflora and Enzymatic Characterization of Fungal Isolates in Commercial Meju, Starter for a Korean Traditional Fermented Soybean Product - Baek, Jin-Ho; So, Kum-Kang; Ko, Yo-Han; Kim, Jung-Mi; Kim, Dae-Hyuk (Mycobiology, 2014)
Mycoflora was assessed in the commercial meju from four well-separated geographic origins. A total of 112 fungal isolates were identified by phenotypic characteristics and molecular taxonomy using sequencing the internal transcribed spacer of the rDNA and revealed 19 species from 13 genera. Enzymatic characteristics of protease and amylase, and mycotoxin production were analyzed.